Load carrying capacity of partially encased columns for different fire ratings - Fellouh, Abdelkadir (2018)
Partially encased columns have significant fire resistance in comparison with steel bare columns. However, it is not possible to assess the fire resistance of such members simply by considering the temperature of the steel. The presence of concrete increases the mass and thermal inertia of the member and the variation of temperature within the cross section, in both the steel and concrete components. The annex G of EN1994-1-2:20051 allows to calculate the load carrying capacity of partially encased columns, for a specific fire rating time, considering the balanced summation model. New formulas will be proposed to calculate the plastic resistance to axial compression and the effective flexural stiffness. These two parameters are used to determine the buckling resistance. The finite element method is used to compare the results for the elastic critical load and the load carrying capacity of partially encased columns for different fire ratings of 30 and 60 min. This work compares the results from both solution methods, provides the validation of the three-dimensional model and demonstrates that a new design curve should be used for the buckling analysis of partially encased columns.